Case report: Therapeutic potential of Flourishing-Life-Of-Wish Virtual Reality Therapy on Relaxation (FLOW-VRT-Relaxation)—a novel personalized relaxation in palliative care - Woo, Olive K. L.; Lee, Antoinette M. (Frontiers in Digital Health, 2023)
In view of the global aging population and growing need of palliative care, innovative intervention for effective symptom management is of urgent need. Flourishing-Life-Of-Wish Virtual Reality Therapy (FLOW-VRT) is a brief, structured, manualized, and personalized psychological intervention with theoretical foundations based on stress coping theory (Lazarus and Folkman, 1984), self-determination theory (Deci & Ryan, 2000), flow theory (Csikszentmihalyi, 1975), and attention restoration theory (Kaplan, 1995; 2001). With a specific focus on relaxation, FLOW-VRT-Relaxation intends to facilitate adaptive end-of-life coping through delivering personalized relaxation. This paper reports a case study of the application of FLOW-VRT-Relaxation, and discusses its therapeutic potential as a cost-effective method for reducing palliative symptoms by addressing patient's unmet needs.The case study is a 51-year-old Chinese female, diagnosed with advanced cervix cancer, and presented with unmet psychological (i.e., unfulfilled wishes) and physical needs (i.e., pain and fatigue) before FLOW-VRT-Relaxation. To address her unmet needs, FLOW-VRT-Relaxation was delivered by a registered clinical psychologist specialized in palliative care. Need assessment was first conducted, followed by a 10-minute VR travel of Japan as her own choice. Relaxation was verbally coached during VR. Right after VR, consolidation with psychological components including psychoeducation, cognitive and emotional processing, and reminiscence intervention were delivered. The patient showed improvement in physical and psychological symptoms, lower sense of loneliness and engulfment, as well as enhanced peace after FLOW-VRT-Relaxation.The current findings provide encouraging initial support for the feasibility, acceptability, and therapeutic potential of using FLOW-VRT-Relaxation as a cost-effective, scalable and personalized VR relaxation for patients under palliative care. It is hoped that with its optimal use, FLOW-VRT-Relaxation can serve as an alternative therapeutic tool that effectively improves the end-on-life care.